Analysis of Tapioca Flour Production Process Control at PT. Florindo Makmur - Irma Damai Yanti; Vidi Agung Fragastia; Syahputra Amri (LPPM Universitas Potensi Utama, 2025)
There are obstacles in the tapioca flour processing process at PT. Florindo Makmur, namely production capacity has not been utilized properly because the supply of raw materials and the public's interest in planting cassava affects tapioca production. The smoothness of the production process will not run smoothly if the control of raw materials does not match customer demand, therefore controlling raw material inventory is very important for the company. In order to meet the uncertainty of consumer orders. One step that can be taken so that smooth production continues to run optimally is to design good and correct raw material inventory control. Therefore, based on the considerations above, it is hoped that the company can build cooperation with suppliers. From this problem, the researcher conducted a problem analysis to predict whether the supply of cassava raw materials at PT. Florindo Makmur has a positive effect on its production process. To solve the existing problem, the following calculation analysis is needed: Linear regression method analysis, Partial Hypothesis Test (t-Test), Determination Coefficient Test (R2). Based on the research that has been conducted on the analysis of the problem to determine the effect of cassava raw material inventory on the tapioca flour production process at PT. Florindo Makmur, the following conclusions can be drawn: The results of the linear regression calculation in 2023 obtained a value of Y = -31.707 + 0.261X and in 2024 obtained a value of Y = -165.529 + 0.274X. The results of the partial calculation (t-test) in 2023 obtained a t-count value of 87,072 and in 2024 obtained a t-count value of 58,148. The results of the calculation of the coefficient of determination (R2) in 2023 were 99.9% and in 2024 were 99.7%. Based on the results of this study, PT. Florindo Makmur is expected to be able to determine the amount of safety stock that must be in the warehouse to anticipate a shortage of cassava raw materials and result in the production process being stopped for 1 or 2 days. PT. Florindo Makmur should work together with farmers to provide training on good cassava planting issues so as to provide good harvest results. This can maintain the availability of raw materials and the sustainability of the production process of PT. Florindo Makmur